Analisa Peran Employee Engagement Dalam Memediasi Work Environment, Leadership, Work Motivation, Job Satisfaction, Dan Training and Development Terhadap Employee Performance Bank Umum - Jennifer Jennifer; Dhita Hafizha Asri (Jurnal Manajemen Bisnis Performa, 2022)
Employee engagement is needed to improve the performance of company resources to compete. Employees who feel engaged are one of the keys to the company's success. This study aims to analyze the role of employee engagement in mediating the work environment, leadership, motivation, job satisfaction, and training and development on employee performance. The population and sample of this study were employees of 5 commercial banks with the most assets in Batam City, Indonesia, namely BRI, Mandiri Bank, BCA, BNI, and BTN. The total number of respondents who were collected using the quota sampling method was 353 with a spread of 80 respondents from each bank. The data obtained from the distribution of the questionnaires were processed using PLS-SEM (Partial Least Square). In the results of the study, employee engagement and work environment have a positive significant effect on employee performance and employee engagement successfully mediates the relationship between work environment and employee performance, while training and development, leadership and job satisfaction have no effect on employee performance but are significantly positive when mediated through employee engagement. Motivation variable has no direct or indirect effect on employee performance. The limitations of this study are that the research sample has not been able to represent the population as a whole and the distribution of the questionnaire only uses 1 alternative.